Amiselimod, a novel sphingosine 1‐phosphate receptor‐1 modulator, has potent therapeutic efficacy for autoimmune diseases, with low bradycardia risk. (17th November 2016) - Sugahara, Kunio; Maeda, Yasuhiro; Shimano, Kyoko; Mogami, Akira; Kataoka, Hirotoshi; Ogawa, Kei; Hikida, Kumiko; Kumagai, Hiroshi; Asayama, Mahoko; Yamamoto, Toshinobu; Harada, Tomohiko; Ni, Pingping; et al.
Abstract : Background and Purpose: We conducted preclinical and clinical studies to examine the pharmacological, particularly cardiac, effects of amiselimod (MT‐1303), a second‐generation sphingosine 1‐phosphate (S1P) receptor modulator, designed to reduce the bradycardia associated with fingolimod and other S1P receptor modulators. Experimental Approach: The selectivity of the active metabolite amiselimod phosphate (amiselimod‐P) for human S1P receptors and activation of G‐protein‐coupled inwardly rectifying K + (GIRK) channels in human atrial myocytes were assessed. Its cardiac distribution was determined in rats, and cardiovascular telemetry was assessed in monkeys. We also examined the pharmacokinetics, pharmacodynamics and safety of amiselimod in healthy humans. Key Results: Amiselimod‐P showed potent selectivity for S1P1 and high selectivity for S1P5 receptors, with minimal agonist activity for S1P4 and no distinct agonist activity for S1P2 or S1P3 receptors and approximately five‐fold weaker GIRK activation than fingolimod‐P. After oral administration of amiselimod or fingolimod at 1 mg·kg −1, the concentration of amiselimod‐P in rat heart tissue was lower than that of fingolimod‐P, potentially contributing to the minimal cardiac effects of amiselimod. A telemetry study in monkeys confirmed that amiselimod did not affect heart rate or ECG parameters. In healthy human subjects, peripheral blood lymphocyte counts gradually reduced over the 21 day dosing period, with similar lymphocyte count profiles with the highest doses by day 21, and no clinically significant bradycardia observed on day 1 or during the study. Conclusions and Implications: Amiselimod exhibited potent therapeutic efficacy with minimal cardiac effects at the anticipated clinical dose and is unlikely to require dose titration.